Physical Activity, Sedentary Behaviour and Other Health Outcomes in People Following Restrictive Bariatric Surgery - Zabatiero, Juliana Gomes (Curtin University, 2016)
Two separate samples of obese adults scheduled to undergo restrictive bariatric surgery participated in two studies that comprised this programme of research. There were no changes from pre-surgery in measures of physical activity (PA) and sedentary behaviour collected over the first 12 months post-surgery, despite large and significant weight loss. People who undergo restrictive bariatric surgery continue to have low motivation and experience barriers to PA, which can inform much needed interventions to optimise PA.